THE HIERARCHY OF INFLUENCE IN RELIGIOUS NEWS COVERAGE AND ITS IMPLICATIONS FOR ISLAMIC COMMUNITY DEVELOPMENT DURING THE 2019 INDONESIAN PRESIDENTIAL ELECTION - Kumarudin, Kumarudin; Heryanto, Gun Gun (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the hierarchy of influence in religious news coverage on Republika.co.id and JawaPos.com during the 2019 Indonesian Presidential Election and its implications for Islamic community development. The Hierarchy of Influence model, developed by Pamela J. Shoemaker and Stephen D. Reese, is employed to analyze the multi-level factors shaping religious media content. This qualitative research uses text observation, interviews, and documentation to identify the influences affecting religious reporting in both online media platforms. The findings reveal that Republika.co.id actively highlighted particular religious issues during the election, while JawaPos.com presented religious coverage in a more sporadic manner. Religious news production in both media outlets was shaped by influences at the individual, routine, organizational, extra-media, and ideological levels. At the individual level, journalists were influenced by Islamic values, professional norms, and worker orientations. At the organizational level, Republika.co.id was influenced by media ownership involvement in political networks, while JawaPos.com demonstrated limited ownership intervention. Extra-media influences, particularly political interest groups, were more visible in Republika.co.id. At the ideological level, both media outlets maintained hegemonic narratives that shaped public perception and religious discourse. This study highlights the strategic role of media in constructing religious narratives within Muslim society and emphasizes the importance of responsible religious reporting to foster social cohesion, democratic participation, and sustainable Islamic community development.